Ler para ser: um desafio possível no cotidiano escolar - Santos, Ivanete de Almeida (2010)
Placed within the Applied Linguistic field, this thesis aims at investigating my action as a teacher in a new reading social practice, called Group Think Aloud (Zanotto, 1998). The research was developed as part of the GEIM Research Group (Indeterminacy and Metaphor Study Group), which is coordinated by Dr. Mara Sophia Zanotto (PUC-SP Pontifical Catholic University of Sao Paulo) and Dr. Heronides M. Moura (UFSC Federal University of Santa Catarina). The theoretical framework that supports this investigation encompasses studies on the teaching-learning theories based on Freire (2005) and Vigotski (1934); theories about critical literacy and critical reading as supported by Freire (1996,2005) Kleiman (2007), Soares (2006) and Solé (1998); and multiple readings as discussed by Zanotto(2008) and Kempe (2001). The study follows qualitative interpretive methodology (Bortoni-Ricardo, 2008), and uses the critical action-research (Kincheloe, 1997 and Barbier, 2004) of ethnographic basis. The instrument used to generate data was the practice of Group Think Aloud (Zanotto, 1998) used in this research both as data-generating instrument and as pedagogic tool. The research was developed with a focal group (Gatti, 2005) composed of 10 students from the 2nd and 3rd grades of High School studying in a state school in Sao Paulo. Data analysis showed the following results: 1) students became more critical about their reading after the practice of Group Think Aloud which allowed for the interaction and negotiation of several readings; 2) the teacher-researcher transformed her teaching practice, taking on a role of mediator and literacy agent that understands that continuous education is the best way to keep up with the new educational paradigms